PH salival antes y después de la ingesta de una bebida típica horchata en niños de 7 a 8 años de edad de la Escuela Marieta de Veintimilla de la ciudad de Loja en el periodo marzo - julio 2015 - Vélez Chuquimarca, Hoover Mauricio (2015)
Study of type quantitative, exploratory, descriptive, non-experimental and cross-sectional design. Wherein the salival pH before and after the consumption of a typical beverage (horchata) in children 7-8 years of age from "Marieta de Veintemilla" school was valued. The sample was comprised of a total of 35 participants, prior authorization of parents or legal representatives with the signature of informed consent to those who underwent salivary pH measurements with a sensitive strip before and after the intake of homemade horchata drink (Sureñita) and packaged (Forestea) foresaw regular tooth brushing with toothpaste (Fortident). The data were registered in tables previously drawn up by the author. The results indicate that 45.7% of the children obtained a pH value of 6.25 after the ingestion of homemade horchata; unlike the Forestea packaged horchata which caused a minor decrease in the pH to 4.5 corresponding to an 8.5%. Concluding that the Forestea packaged horchata produces a noticeable salivary pH descent compared to the homemade horchata Sureñita. Keywords: forestea - Saliva - Sureñita